PENGARUH PETA PEMIKIRAN (THINKING MAP) DALAM PEMBELAJARAN BERBASIS MASALAH TERHADAP PENGUASAAN KONSEP DAN LITERASI SAINS SISWA SMP - Hanim, Latifah; Susilo, Herawati; Yuliati, Lia (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to determine the effectiveness of PBL with thinking map on the mastery of the concept and students' scientific literacy in digestive system material, additives and addictive substances, and respiratory system in human. This quantitative study involved 94 students consisting of 3 classes, namely 31 students of class VIII C, 31 students of class VIII E and 32 students of class VIII A SMP Negeri 5 Jombang academic year 2018/2019. Data was collected using test and non-test techniques through the observation sheet. Then the data were analyzed descriptively and inferential statistics with ancova to determine the effectiveness of PBL assisted with thinking map, as well as effect size test to find out how much influence the thinking map had with the help of SPSS 16. The results showed PBL assisted thinking map effective on mastering the concept of content dimensions and against scientific literacy in digestive system material, additives and addictive substances, and the respiratory system. The results of statistical tests showed that there were differences in the mastery of concepts and scientific literacy skills before and after using PBL assisted by thinking map on digestive system material, additives and addictive substances, and the respiratory system. The conclusion of this study is that problem-based learning assisted by thinking map has an effect on both mastery of science concepts and science literacy so that students are effectively used in junior high school on digestive system material, additives and addictive substances, and the respiratory system.Abstrak: Penelitian ini bertujuan mengetahui keefektifan PBM berbantuan thinking map terhadap penguasaan konsep IPA dan literasi sains siswa SMP pada materi sistem pencernaan, zat aditif dan adiktif, dan sistem pernapasan pada manusia. Penelitian kuantitatif ini melibatkan 94 peserta didik terdiri atas 3 kelas, yaitu 31 peserta didik kelas VIII C, 31 peserta didik kelas VIII E dan 32 peserta didik kelas VIII A SMP Negeri 5 Jombang tahun ajaran 2018/2019. Data dihimpun menggunakan teknik tes dan non-tes melalui lembar observasi. Kemudian data dianalisis secara deskriptif dan statistik inferensial dengan ancova untuk mengetahui keefektifan PBM berbantuan thinking map, serta uji effect size untuk mengetahui berapa besar pengaruh thinking map dengan bantuan SPSS 16. Hasil penelitian menunjukkan PBM berbantuan thinking map efektif terhadap penguasaan konsep dan literasi sains pada materi sistem pencernaan, zat aditif dan adiktif, dan sistem pernapasan. Hasil uji statistik menunjukkan terdapat perbedaan penguasaan konsep dan kemampuan literasi sains sebelum dan setelah menggunakan PBM berbantuan thinking map. Kesimpulan penelitian ini adalah pembelajaran berbasis masalah berbantuan thinking map berpengaruh baik pada penguasaan konsep IPA dan literasi sains siswa sehingga efektif digunakan di SMP pada materi sistem pencernaan, zat aditif dan adiktif, dan sistem pernapasan.